Unveiling the ethnomathematics in Yogyakarta's Sultan palace architecture - Yudhiartika, Fatmarani; Utami, Niken Wahyu (Universitas Papua, 2024)
The architecture of the Sultan's Palace in Yogyakarta offers a compelling opportunity to engage students in mathematics education while simultaneously contributing to preserving and promoting local cultural heritage from an early age. This research aims to explore the ethnomathematics embedded within the architectural design of Yogyakarta’s Sultan Palace to facilitate elementary school students' comprehension of mathematical concepts, particularly those related to numbers. Employing a qualitative approach, this study investigates the ethnomathematical dimensions of the Sultan's Palace architecture through comprehensive observation and analysis. The methodology involves examining the architectural features, identifying conceptual underpinnings, and establishing criteria to validate the traditional practices embodied in the palace's design. Based on these findings, new criteria for mathematics education are proposed. The research focuses on various elements of the Sultan’s Palace, including Kemandungan Lor/Plataran Keben, Bangsal Pancaniti, Regol Bangsal Pancaniti, Bangsal Sri Manganti, Penjagen Dragunder, Bangsal Manis, Bangsal Mandhasana, Ward Kotak, Gedhong Jene, Kasatriyan, Bangsal Kencana, and Danapratapa Gate. The results indicate that the architectural features of the Sultan’s Palace offer valuable insights into teaching mathematical concepts across several domains, such as numbers, algebra, measurement, geometry, data analysis, and probability. Specifically, the study aims to uncover geometric patterns, shapes, and principles integrated into the palace’s design. This research contributes to cultural preservation by documenting and analyzing the application of mathematics in the Sultan's Palace architecture—an aspect often neglected. Additionally, the findings hold significant implications for education by providing innovative teaching materials that intertwine cultural and mathematical elements, thereby enhancing students' understanding of mathematical concepts.